Assessment of age-related change of the ocular support system - Makarem, Ahmed; Abass, Ahmed; Bao, Fangjun; Elsheikh, Ahmed (Frontiers in Bioengineering and Biotechnology, 2023)
To estimate the material stiffness of the orbital soft tissue in human orbits using an inverse numerical analysis approach, which could be used in future studies to understand the behaviour under dynamic, non-contact tonometry or simulate various ophthalmological conditions. Clinical data were obtained for the left eye of 185 Chinese participants subjected to a complete ophthalmic examination, including tests by the Corvis ST and Pentacam. 185 numerical models of the eye globes were built with idealised geometry of the sclera while considering the corneal tomography measured by the Pentacam. The models were extended to include representations of the orbital soft tissue (OST), which were given idealised geometry. The movement of the whole eye in response to an air-puff directed at the central cornea was examined and used in an inverse analysis process to estimate the biomechanical stiffness parameters of the OST. The results indicated a weak correlation of E t with the progression of age, regardless of the stress at which E t was calculated. However, there was evidence of significant differences in E t between some of the age groups.There was statistical evidence of significant differences between E t in the age range 20 < years < 43 relative to E t in OST with age ranges 43 < years < 63 (p=0.022) and 63 < years < 91 (p=0.011).In contrast, E t in OST with age ranges 43 < years < 63 and 63 < years < 91 were not significantly different (p= 0.863). The optimised mechanical properties of the OST were found to be almost four times stiffer than properties of fatty tissue of previous experimental work. This study consolidated previous findings of the role of extraocular muscles on the ocular suppor system. In addition, the rotation of the globe during corvis loading is suggested to be of posterior components of the globe and shall be firther investigated. 1 Assessment of Age-related Change of the ocular support system Frontiers